1977
DOI: 10.3109/10520297709116752
|View full text |Cite
|
Sign up to set email alerts
|

A Silver Impregnation Method for Nervous Tissue Suitable for Routine use with Mounted Sections

Abstract: A simple, reliable silver impregnation method for nervous tissue is described for tissues fixed in various fixatives including formalin, Bouin, and Susa. Sections are impregnated in a solution containing 1 g Protargol, 2 ml of a 1% Cu(NO3)2 solution, 2 ml of a 1% AgNO3 solution, and 2-4 drops 30% H2O2 in 100 ml distilled water. Sections are impregnated 2-5 days at 37 C and thereafter reduced in a hydroquinone-formalin solution. This is followed by gold toning and subsequent reduction, dehydration and mounting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Serial sections 10 pm in thickness were cut in a plane parallel to the upper margin of the lower bill. They were stained by the silver impregna-tion method of Loots et al (1977) and observed under light microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Serial sections 10 pm in thickness were cut in a plane parallel to the upper margin of the lower bill. They were stained by the silver impregna-tion method of Loots et al (1977) and observed under light microscopy.…”
Section: Methodsmentioning
confidence: 99%